2018
DOI: 10.1111/pbr.12585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod sensitivity genes Ppd‐B1 and Ppd‐D1 on spike fertility and related traits in bread wheat

Abstract: Increasing grain yield is a key breeding goal in bread wheat. Several authors have suggested that a spike fertility index (SF), that is the quotient between grain number per unit spike (GNS) and spike chaff dry weight (SCDW), could be used as a yield-related selection criterion, especially if molecular markers were available. Here, the effects of Ppd-B1 and Ppd-D1 genes on SFm, GNSm and SCDWm (measured at maturity) and the relationship between these variables were analysed in field experiments carried out duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The first thing we did was to determine the correlation between FEm values as taken in F2, F3 and RILs (advanced lines without selection). As a result, positive, significant correlations were observed (rF2-F3=0.46; rF2-RILs=0.32; rF3-RILs=0.32; P<0.05); this was not surprising, considering the high heritability of the trait (González et al, 2011;Martino et al, 2015;Mirabella et al, 2016;Alonso et al, 2018b;Ramirez et al, 2018;Pretini et al, 2020;Pontaroli et al, 2021). Nevertheless, it was encouraging to find these correlations considering that F2 and F3 plants are highly heterozygous, and measurements were taken on individual plants or rows as opposed to the sampling done in advanced generations, which entailed drawing a random spike sample from yield plots in homozygous lines.…”
Section: Discussionmentioning
confidence: 76%
“…The first thing we did was to determine the correlation between FEm values as taken in F2, F3 and RILs (advanced lines without selection). As a result, positive, significant correlations were observed (rF2-F3=0.46; rF2-RILs=0.32; rF3-RILs=0.32; P<0.05); this was not surprising, considering the high heritability of the trait (González et al, 2011;Martino et al, 2015;Mirabella et al, 2016;Alonso et al, 2018b;Ramirez et al, 2018;Pretini et al, 2020;Pontaroli et al, 2021). Nevertheless, it was encouraging to find these correlations considering that F2 and F3 plants are highly heterozygous, and measurements were taken on individual plants or rows as opposed to the sampling done in advanced generations, which entailed drawing a random spike sample from yield plots in homozygous lines.…”
Section: Discussionmentioning
confidence: 76%
“…The effect of the Ppd genes, reported by Ramirez et al (2018) as being associated with SF, could not be evaluated in this population because their parents, B10 and KCJ, are monomorphic for these genes (Vanzetti et al 2013). Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…As for SF at maturity, Guo et al (2017) found a QTL on chromosome 2A, with a relatively small effect. Ramirez et al (2018) reported significant yet small effects of Ppd-B1 and Ppd-D1 on SF at maturity that were independent from those on the flowering date. Recently, a GWAS conducted by Pradhan et al (2019) allowed identification of 15 markertrait associations (MTAs) with SF in chromosomes 1B, 3B, 4A, 6B, and 7D.…”
Section: Introductionmentioning
confidence: 90%
“…However, PPD-D1 was found to have an impact on SF under SSC, with Ppd-D1a allele increasing SF by 10.6%. In a study examining the impact of photoperiod sensitivity on SF, the PPD-B1 and PPD-D1 genes’ insensitive alleles were found to be linked to an increase in SF (Ramírez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding whether there are differences in the effects of the allelic variants of VRN-1 and PPD-1 genes on phenology and agronomical traits across autumn and spring sowing conditions, will be important for their proper utilization. Unfortunately, only few studies have been carried out in this regard (Steinfort et al, 2017; Ramírez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%